Impact of feeding urea ammoniated and urea supplemented wheat straw on intake and utilization of nutrients in crossbred cattle - Verma, A K; Singh, P; Dass, R S; Mehara, U R (The Indian Journal of Animal Sciences, 2011)
Adult male crossbred cattle (12), weighing on average 382±5.41 kg, were assigned to 3 equal groups in a completely randomized design and fed-wheat straw (WS) in group 1, urea-ammoniated wheat straw (UAWS) in group 2 and urea supplemented wheat straw fUSWS) in group 3, respectively, along with concentrate mixtures of varying crude protein content to meet their nutrients requirements. Intake of all the nutrients was significantly higher in group 2 as compared to groups I and 3. However, in group 2 the digestibility of OM, OM and total carbohydrates was similar to control group I but it was significantly lower in group 3 as compared to other 2 groups. Moreover, significantly lower digestibility of CP and significantly higher digestibility of EE, NOF, AOF and cellulose was observed in group 2. Nutrients intake (g/d and g/kgWIl75) were significantly higher in groups 2 and 3 as compared to group I except OM intake. OCP content of the diets was significantly higher in group 3 in comparison to groups] and 2 (WS and UAWS) but the intake ofTON was significantly higher in group 2. Intake ofN was significantly higher in groups 2 and 3 as compared to group I and intake ofCa was also significantly higher in group 2. However, the balances ofN and Ca were positive and significantly higher in groups 2 and 3 as compared to group 1, whereas, intake and balance ofP did not differ significantly among 3 groups. Feeding of urea ammoniated wheat straw showed significantly higher OM intake, digestibility and balances of nutrients in crossbred cattle, which was followed by urea supplemented wheat straw fed group. Hence, feeding of UAWS and USWS may be recommended in the diets of cattle to economize the cost ofconcentrate by reducing 22% deoiled groundnut cake.